Nutritive value and effect of different levels of Leucaena hay on intake and apparent digestibility of ration - Costa, Emanuel Sousa; de Souza, Antônio Alves; Neto, Francisco Bezerra; Melo Lima, Francisco de Assis; Pereira, Raimundo Mauro Araripe (Pesquisa Agropecuaria Brasileira, 2014)
A trial was conducted to determine the nutritive value of Leucaena leucocephala (Lam) de Wit, hay, the effect of different levels of that hay on apparent digestibility intake and nitrogen balance. Twenty castrated males “Morada Nova” breed sheeps, average weight 25 kg, were utilized. The experimental period was 21 days, 14 for diet adaptation and 7 for data collection. Five completely randomized blocks with five hay levels (0, 25, 50, 75 and 100%) with four replication were used, complemented with cornear straw. Results were evaluated through regression analysis. Chemical composition of hay on dry matter (DM), 91.35%; crude protein (CP), 18.10%; crude fiber (CF), 29.14%; fat matter (FM), 2.20%; crude energy (CE), 4365 Kcal/kg; ashes, 6.14%; calcium, 1.18% and phosphorus, 0.29%. Apparent digestibility coefficients were: DM = 57.37%; CE = 54.96%; CF = 60.64% and CP = 58.63%. Leucaena leucocephala hay is very palatable and can promote sensible increase of dry matter intake when combined to low nutritive value forages, e.g. straw. Leucaena leucocephala association with cornear straw increased apparent ration digestibility. Optimum estimated level of hay in the ration was 61.80% for digestible intake.